Childhood Brucellosis; Three Cases from North Karnataka - Nagmoti1*,CS Patil2, Jyoti.M.Nagmoti1, Mutnal MB1; Mubashir Anagolkar3, M.B. (Recent Research in Science and Technology, 2011)
Brucellosis is a zoonotic disease and endemic in Belgaum. It is characterized by myriad of nonspecific symptoms like fever, nocturnal sweating, backache, osteoarticular symptoms along with complications. Clinical presentation of this infection is variable as it may manifest a systemic disease. Herewith we present three cases of blood culture positive B. mellitensis in pediatric patients. Routine screening for Brucellosis by slide agglutination test can be more helpful in diagnosing PUO.